1991
DOI: 10.1002/j.1460-2075.1991.tb07843.x
|View full text |Cite
|
Sign up to set email alerts
|

Several different upstream promoter elements can potentiate transactivation by the BPV-1 E2 protein.

Abstract: The enhancer and upstream promoter regions of RNA polymerase II transcribed genes modulate the rate of transcription initiation and establish specific patterns of gene expression. Both types of region consist of clusters of DNA binding sites for nuclear proteins. To determine how efficiently the same factor can activate transcription when acting as an enhancer or promoter factor, we have studied transactivation by the BPV‐1 E2 protein, a papillomavirus transcriptional regulator. By cotransfecting a BPV‐1 E2 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
1
2

Year Published

1992
1992
2002
2002

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 61 publications
3
42
1
2
Order By: Relevance
“…2 Previous studies have shown that a core promoter must contain at least two elements to be able to respond to E2 and that such elements, the TATA box, the initiator element, or a binding site for an upstream promoter factor, are interchangeable to a large extent (33). Therefore E2 requires the co-operation of at least one additional DNA binding proximal promoter factor, such as Sp1, or other factors that interact with papillomavirus promoters, such as AP-1, Oct-1, NF-1/CTF, or USF for the activation of a minimal TATA box promoter (28,34). Epithelial-specific functions of some of these factors have emerged.…”
Section: Discussionmentioning
confidence: 99%
“…2 Previous studies have shown that a core promoter must contain at least two elements to be able to respond to E2 and that such elements, the TATA box, the initiator element, or a binding site for an upstream promoter factor, are interchangeable to a large extent (33). Therefore E2 requires the co-operation of at least one additional DNA binding proximal promoter factor, such as Sp1, or other factors that interact with papillomavirus promoters, such as AP-1, Oct-1, NF-1/CTF, or USF for the activation of a minimal TATA box promoter (28,34). Epithelial-specific functions of some of these factors have emerged.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid pC18-SP1-luc (a kind gift of G. Steger, Institute of Virology, Cologne, Germany) consists of four synthetic E2 binding sites (5Ј-CTAGACCGAAAACGGTG-3Ј) and two synthetic SP1 binding sites (5Ј-GATCTAAACCCCGCCCAGCCG-3Ј) upstream of a minimal adenovirus major late promoter composed of the TATA box and the initiator element inserted into the luciferase reporter plasmid pALuc (G. Steger, unpublished data). Plasmid pC18-luc, which is comparable to plasmid pC18 (19), was constructed by removing the SP1 binding sites from pC18-SP1-luc by BamHI digestion. E2 and SP1 binding sites were deleted from plasmid pC18-luc by digesting with HindIII and BamHI, filling in the ends with Klenow polymerase, and religating the fragments.…”
Section: Methodsmentioning
confidence: 99%
“…Repression of HPV gene expression by the E2 activator protein occurs when E2 binding sites are overlapping with the binding sites for cellular transcription factors necessary for promoter activity. In contrast to natural HPV promoter-enhancer constellations E2 can strongly activate synthetic promoters containing several E2 binding sites upstream of a promoter, although specific differences in the mode of activation between the E2 proteins of different types may exist (18,27,61). In addition to its role in regulation of gene expression, E2 is also necessary for viral DNA replication.…”
mentioning
confidence: 99%